STRATEGIC BRAND IDENTITY DESIGN FRAMEWORK FOR MICRO AND SMALL-SIZED DESIGN COMPANIES - Rudi Yulio Arindiono (Journal of Scientech Research and Development, 2024)
Micro and small design companies often face resource constraints, leading to limited diversification in skillsets. This forces team members to take on multiple roles, such as combining consulting, strategy, and creative direction. The research aims to support these companies by developing an easy-to-use strategy kit to assist in brand identity creation projects. The study introduces a new framework, serving as the foundation for a toolkit, and focuses on examining brand identity design theories while integrating them with design thinking methods. The goal is to help micro-enterprises build strong brand identities that align with their client's vision and customer needs. The framework is based on David Aaker’s Brand Identity Planning Model, emphasizing the Brand Identity System, including core and extended identity, value proposition, and brand-customer relationships. Aaker’s Strategic Brand Analysis, which covers customer, competitor, and self-analysis, is also briefly discussed as a foundation for understanding the client and the initial stages of branding. The study employed a qualitative analytical approach, using case studies and interviews to gather data. The findings led to the development of a new framework for brand identity creation, with conclusions drawn from the study’s evaluation and findings.